Perancangan UI/UX Aplikasi Mobile Marketplace Barbershop Barbergo Dengan Metode User Centered Design - Nasywa Zahira Ramadhani; Seftin Fitri Ana Wati; Anindo Saka Fitri (Direktorat Riset dan Pengabdian Pada Masyarakat (DRPM) Universitas Bina Darma, 2025)
This research aims to produce interface design solutions and user experience for the mobile application of the BarberGo barbershop marketplace using the User Centered Design method. The research method used involves four main stages of User Centered Design consisting of Understand and Specify The Context of Use, Specify The User Requirements, Produce Design Solutions, and Evaluate The Design Against Requirements. Data collection through literature study methods and interviews with each of the five customer and barbershop respondents. The interview results were then processed and analyzed to obtain interface design solutions that have good usability values. The results of this study show a significant comparison between the results of the usability evaluation in the first and second stages. In the results of the usability level evaluation, from the customer side there was an increase in usability value of 18.16% with a final result of 80.74% and the barbershop experienced an increase in usability value of 17.19% with a final result of 82.28%. In the evaluation results of the System Usability Scale (SUS), from the customer side, there was an increase in value of 27 with a final result of 93 and the barbershop experienced an increase in value of 26 with a final result of 94. Based on these results, it shows that the interface design of the BarberGo barbershop marketplace mobile application has a good level of usability, and can be accepted and is suitable for use by users.